Composite Rolling Test Control Method of Gear and Software - Guo Xiaodong; Zhang Hongli; Zhang Weiqing; Wang Ge; Huang Gang (Jixie chuandong)
The principle of double- flank gear measuring is usually adopted by gear screening equipment in workshop. The real quality of gear transmission cannot be obtained because of the test result containing manufacture error in both sides of tooth. To solve this problem,a new type of gear comprehensive roll testing method is studied,combining the gear double meshing gear radial comprehensive deviation detection with the single meshing vibration noise detection,the quality of gear transmission can be comprehensively evaluated. The key techniques,such as automatically aligning tooth,automatic backlash adjust,electric closed coupling loading,measuring and analysis are solved. The complement software is developed,which is applied on YKZ9932 machine manufactured by Tianjin No. 1 Machine Tool Works. According to the test result,the gear transmission quality is reflected more systematically by using this new method.